Effect of Proportion of Sorbitol and Sucrose with Pectin Concentration to Physicochemical and Sensoric Characteristics of Pedada Jam Gelato (Sonneratia caseolaris) - Salsabila Ayu Sukma; Jariyah Jariyah (International Journal on Food, Agriculture and Natural Resources, 2022)
Gelato is a frozen dessert that has lower fat and overrun content and higher sugar content than ice cream. Sorbitol can affect the texture of gelato and has lower glycemic index and calories than sucrose. Sucrose provides sweetness without cooling effect therefore it can balance the sweetness of gelato. Pectin can affect the melting speed and produce better stability of product. The addition of pedada fruit jam was to improve aroma, taste and nutrition. This study aimed to determine the effect of  proportion of sorbitol and sucrose with the concentration of pectin on the physicochemical and sensoric properties of pedada jam gelato. The experimental design used was  completely randomized design with two factors. Factor I was the proportion of sorbitol and sucrose (13:2, 12:3, 11:4%) and factor II was the addition of pectin (0.3, 0.5, 0.7%). The analysis parametes were fat content, overrun, melting time, viscosity, total solids, total sugar, soluble fiber, reducing sugar and organoleptic scale scoring test (taste, color, aroma, texture). The best treatment was the proportion of sorbitol and sucrose 11:4% with pectin 0.5% which had fat content 1.77%, overrun 26.97%, melting time 18.07 minutes, total solids 43.19%, viscosity 1577 cP, total sugar 16.68%, soluble fiber 2.16% and reducing sugar 3.63%. The result of the organoleptic scale scoring test showed a taste of 4.32 (sweet), color 3.56 (moderate dark brown), texture 4 (soft), and aroma 3 (moderate pedada fruit aroma).